1991
DOI: 10.1111/j.1600-0609.1991.tb01540.x
|View full text |Cite
|
Sign up to set email alerts
|

A sequential histological study of bone marrow fibrosis in idiopathic myelofibrosis

Abstract: A sequential histological study of bone marrow biopsies from 36 patients with idiopathic myelofibrosis was performed to investigate the accumulation of connective tissue in the bone marrow during the course of the disease and the influence of therapy on this process. The degree of bone marrow fibrosis was graded semiquantitatively from 0 (normal) to + 5 (extensive collagen fibrosis and ostemyelosclerosis). The median interval between the first and final biopsy was 25 months (range 3 to 103) in patients with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Insofar as it identified statistically significant differences between the three degrees of fibrosis as defined here, the present study demonstrates that each of these three degrees corresponds to a different length of reticulin fibres per area of haemopoietic marrow. There is nevertheless a certain amount of overlap between degrees I and Islam 1981;Hasselbach & Lisse 1991); and at present we subclassify grade I11 in grades I11 and IV, the latter if collagen fibres are seen in a trichromic stain (Masson's stain) with any objective. The present study showed excellent agreement between the results obtained by two different raters using the optical method, though the correlation was less strong in the case of grade I.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Insofar as it identified statistically significant differences between the three degrees of fibrosis as defined here, the present study demonstrates that each of these three degrees corresponds to a different length of reticulin fibres per area of haemopoietic marrow. There is nevertheless a certain amount of overlap between degrees I and Islam 1981;Hasselbach & Lisse 1991); and at present we subclassify grade I11 in grades I11 and IV, the latter if collagen fibres are seen in a trichromic stain (Masson's stain) with any objective. The present study showed excellent agreement between the results obtained by two different raters using the optical method, though the correlation was less strong in the case of grade I.…”
Section: Discussionmentioning
confidence: 96%
“…Quantification of reticulin fibres by objective methods such as planimetry (Lennert, Nagai & Schwarze 1975) or sophisticated image analysers (Coasquen et al 1979) is laborious and therefore of little relevance to daily practice. The various methods of assessing the intensity of fibrosis on the basis of purely subjective criteria that have therefore been proposed have not been validated either by objective methods or by studies of inter-rater agreement (Kundel et al 1964 Manoharan, Horsley & Pitney 1979;Islam et al 1981;Dupuy et al 1987;Thiele et al 1987;Hasselbach & Lisse 1991). One of the authors proposed a method of classifying reticulin fibrosis into one of four degrees (grade 0, i.e., no fibrosis, plus grades I, 11, and 111) on the basis of the power of the light-microscope objective required to permit recognition of fibres (Hernandez-Nieto et al 1978).…”
mentioning
confidence: 99%
“…Although PMF may evolve from a stage of hypercellularity with minimal fibrosis to an advanced stage with myeloid atrophy and myelofibrosis, this evolution has not been convincingly proven via sequential bone marrow biopsies during the course of the disease. A few studies have attempted systematically to follow the evolution of bone marrow fibrosis, and highly different results were obtained [193,[196][197][198][204][205][206][207][208][209]. Hasselbalch and Lisse found a constant bone marrow pattern or regression of bone marrow fibrosis to be the most common [209].…”
Section: Histological Studies On Bone Marrow Stroma In Mpnsmentioning
confidence: 99%
“…A few studies have attempted systematically to follow the evolution of bone marrow fibrosis, and highly different results were obtained [193,[196][197][198][204][205][206][207][208][209]. Hasselbalch and Lisse found a constant bone marrow pattern or regression of bone marrow fibrosis to be the most common [209]. This was also recorded in other series [193,196,[204][205][206], even though progressive myelofibrosis was recorded in some studies [198,207,208].…”
Section: Histological Studies On Bone Marrow Stroma In Mpnsmentioning
confidence: 99%